Pengaruh eva (economic value added), roe (return on equity) dan eps (earning per share) terhadap harga saham (studi kasus: pt kimia farma tbk periode tahun 2001 – 2010) - Subarjo Subarjo (Universitas Mercu Buana Yogyakarta, 2013)
The purpose of this research is reference for company pay more attention the fundamental factor in assessing the impact on the company’stock price and ultimately be able provide prospaerity fos stakeholders. Fundamental of factors such as economic value added, return on equity and earning per share don’t effect to stock prices. It is the investor or broker more transaction basd on technical analysis. However. It can be seen from the absence of the influence of fundamental variable partially to changes in stock changes in stock prices in Indonesian Stock Exchange.